2014
DOI: 10.1186/gm560
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles associated with acute myocardial infarction and risk of cardiovascular death

Abstract: BackgroundGenetic risk scores have been developed for coronary artery disease and atherosclerosis, but are not predictive of adverse cardiovascular events. We asked whether peripheral blood expression profiles may be predictive of acute myocardial infarction (AMI) and/or cardiovascular death.MethodsPeripheral blood samples from 338 subjects aged 62 ± 11 years with coronary artery disease (CAD) were analyzed in two phases (discovery N = 175, and replication N = 163), and followed for a mean 2.4 years for cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 33 publications
0
34
0
2
Order By: Relevance
“…The Coronary Artery Disease (CAD) cohort comprised 147 unrelated individuals enrolled in the Emory Cardiovascular Biobank, USA, with suspected or confirmed CAD [32]. RNA was collected from whole-blood samples with expression levels measured in 47,231 genome-wide probes using the Illumina HumanHT-12 Beadchip.…”
Section: Methodsmentioning
confidence: 99%
“…The Coronary Artery Disease (CAD) cohort comprised 147 unrelated individuals enrolled in the Emory Cardiovascular Biobank, USA, with suspected or confirmed CAD [32]. RNA was collected from whole-blood samples with expression levels measured in 47,231 genome-wide probes using the Illumina HumanHT-12 Beadchip.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression and X-chromosome genotype data were available in a subset of N=2,130 individuals (N=1,084 males, N=1,046 females) from the Consortium for the Architecture of Gene Expression (CAGE), a study examining the genetic architecture of gene expression in a mixture of pedigree and unrelated individuals (Lloyd-jones et al, 2017). This subset of individuals comes from three cohorts with genotype data on the X chromosome (Powell et al, 2012(Powell et al, , 2013Kim et al, 2014;Leitsalu et al, 2015), and are of European ancestry, as identified by principal component analysis with the HapMap3 populations. Further details are provided in (Lloyd-jones et al, 2017).…”
Section: Consortium For the Architecture Of Gene Expression (Cage) Datamentioning
confidence: 99%
“…Because of their rapid turnover, tissue protein profiles (as opposed to RNA expression) are more variable, and it is now appreciated that protein, metabolite, and lipid analyses are not as well-suited for systems analyses at the genome-wide level in individual human tissues, given the current state of the technology to measure these different dimensions. However, patterns of protein and metabolite expression in plasma may be an exception (73,74), and integrating RNA expression with protein and metabolite profiles can greatly enhance the predictive power of disease gene networks (75). …”
Section: Systems Genetics-identifying Disease-driving Network and Thmentioning
confidence: 99%